THE INFLUENCE OF DISCOVERY LEARNING AND SNOWBALL THROWING METHOD IN IMPROVIN WRITING SKILLS OF HIGH SCHOOL STUDENTS - Winda Intan Lestari; Ulfah Mawaddah; Evie Kareviati (IKIP Siliwangi, 2019)
The purpose of this study is to analyze the improvement of students' writing skills by using Discovery learning and the Snowball Throwing method. this study uses Quasi-Experimental by comparing two different variables with the stages of giving pre-test, treatment, and post-test and looking for the difference in value using the Gain Test. This research was conducted in class XI of SMK 4 Padalarang LPPM with a sample population of 60 students namely 30 students of class XI RPL 1 as control class and 30 students with discovery learning method and RPL 2 class as Experimental class with Snowball Throwing approach. From the results of this study conclusions are obtained 1). The ability to write students using the Snowball method is effective and better than using discovery learning. 2). There is a change in the value of writing narrative texts of students using the snowball method rather than discovery learning.